Improving Dental Health and Nutrition Awareness through the "SEGIGIKU" School Health Program - Bedjo Santoso (JURNAL INFO KESEHATAN, 2025)
Indonesia faces serious challenges in dental and oral health and nutrition, with dental caries, stunting, and obesity remaining major public health problems among children. Schools play a crucial role in shaping children’s health behaviors through structured health education and interventions. The School Health Program model “SEGIGIKU” was developed to enhance the involvement of teachers, peers, and parents in improving oral health behavior and nutrition awareness as preventive measures against dental caries, stunting, and obesity in preschool children. This study aimed to develop and evaluate the “SEGIGIKU” School Health Program model as an effort to improve oral health behavior and nutrition awareness among preschool children. This research employed a research and development (R&D) design, consisting of stages of information gathering, program design, expert validation, product testing, and final product development. The results showed a consistent weekly increase in students’ weight and height. Statistical analysis using the Wilcoxon test demonstrated a highly significant improvement in dental hygiene, as indicated by the PHPM score (p = 0.000), and a significant reduction in dental caries, as reflected by the decay score (p = 0.002). In conclusion, the “SEGIGIKU” School Health Program model effectively improves oral health behavior and nutrition awareness, which are closely interconnected, and contributes to the prevention of dental caries, stunting, and obesity in preschool children.